Macroscopic hygro-mechanical modeling of restrained ring test: results from COST TU1404 benchmark - Šmilauer, Vit (2018)
The restrained ring test under constant temperature is used for estimating cracking tendency of pastes, mortar or concrete. This test induces hygro-mechanical interactions, with intricate interplay of several phenomena such as autogenous shrinkage, drying shrinkage, basic and drying creep, as well as evolution of tensile strength and fracture energy. The benchmark described in this paper relies on extensive experimental data sets obtained through the extended Round Robin Testing programme (RRT+) of COST Action TU1404. Five teams took part with their simulation models. A series of outputs were produced, starting from mass loss of a prism through its axial deformation up to stress/strain evolution in the ring. Three teams quantified also damage due to drying and stress concentration around a ring’s notch. All models showed excellent performance on mass loss while strain validation showed higher scatter and influence of several other factors. The benchmark demonstrated high capability of used models and emphasized strong role of calibration with regards to available experimental data.